The end that does art, science, and millennial accomplishment - Gutierrez, Cathy, 1967-; Schwartz, Hillel, 1948- (London ; Oakville : Equinox Pub., 2006)
Millennial movements do not always go boom and bust. As innovative responses to worlds in crisis or projections of possibilities for a world in the doldrums, millennialism has been a prime mover for many an artistic and scientific vision of the world reconfigured. Flourishing well beyond the life of any prophet, bearing fruit well beyond the waning of any redemptive scheme, these visions merit a history of their own. The End that Does tracks the interplay of the arts, the sciences, and millennial imagination across 3000 years of surprising conclusions.
Will (poem) / Thomas MacKay -- In/tensions / Cathy Gutierrez -- Part I: At/tension. The pharmakon of the apocalypse / Kelli Fuery and Patrick Fuery -- The merit of time : a genealogy of the countdown / Hai Ren -- Postcard I (poem) / Thomas MacKay -- Part II: Re/tension. Collecting the cosmos : the apocalypse of the ancient library / Eric Casey -- Giordano Bruno and the rewriting of the heavens / Geoffrey McVey -- Francis Bacon's scientific apocalypse / Steven Matthews -- Promise (poem) / Thomas MacKay -- Part III. De/tension. The elusive Isis : theosophy and the mirror of millennialism / Cathy Gutierrez -- Promiseland : utopian technology and the American millennial dream / Fred Nadis -- Postcard II (poem) / Thomas MacKay -- Part IV. Dis/tension. The end is still near : the eternal apocalypse of the tabloids / Amelia Carr -- Christian apocalyptic fiction, science fiction, and technology / Tom Doyle -- Unto (Rose Window, Sainte-Chapelle, Paris) / Thomas MacKay -- Part V. Tense. Y2KO to Y2OK / Charles Cameron -- Cloister (poem) / Thomas MacKay -- Respite (poem) / Thomas MacKay -- Part VI. Ex/tension. The Space Needle hits the road : the portability of home, landmark and memorial / Michelle Dent -- Ultima Thule--the city at the end of the world : Jerusalem in the modern Christian apocalyptic / Hillel Schwartz -- International radio / Thomas MacKay.
Includes bibliographical references and index.
Keywords: Millennialism -- Congresses; Religion and culture -- Congresses; Millennialism; Religion and culture; Chiliasmus; Jahrtausendwende; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; RELIGION / Theology; Electronic books; Conference proceedings